Inner transformation to sustainability as a deep leverage point: fostering new avenues for change through dialogue and reflection - Woiwode, Christoph; Schäpke, Niko; Bina, Olivia; Veciana, Stella; Kunze, Iris; Parodi, Oliver; Schweizer-Ries, Petra; Wamsler, Christine (Sustainability science, 2021)
This article provides a rationale for inner transformation as a key and hitherto underresearched dimension of sustainability transformations. Inner transformation relates to various aspects of human existence and interactions such as consciousness, mindsets, values, worldviews, beliefs, spirituality and human–nature connectedness. The article draws on Meadows’ leverage points approach, as places to intervene in a system, to reveal the relevance of inner transformation for system change towards sustainability. Based on insights from a series of dialogue and reflection workshops and a literature review, this article provides three important contributions to sustainability transformations research: first, it increases our conceptual understanding of inner transformation and its relevance for sustainability; second, it outlines concrete elements of the inner transformation-sustainability nexus in relation to leverage points; and third, it presents practical examples illustrating how to work with leverage points for supporting inner transformation. In sum, the paper develops a systematized and structured approach to understanding inner transformation, including the identification of deep, i.e., highly influential, leverage points. In addition, it critically discusses the often contentious and divergent perspectives on inner transformation and shows related practical challenges. Finally, current developments in inner transformation research as well as further research needs are identified.